2006
DOI: 10.1080/09273940600977241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Levels of Serum Antibodies to Gram Negative Microorganisms in Turkish Patients with HLA-B27 Positive Acute Anterior Uveitis and Controls

Abstract: Serum antibody positivity against Yersiniae enterocolitica, Campylobacter jejuni and Chlamydia trachomatis is not frequent in the HLA-B27 positive and negative AAU patients. Serum levels of IgM, IgG, and IgA antibodies also did not show significant difference between three groups. No association between these microorganisms and the etiology of AAU was evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…pylori in the development and recurrence of HLA-B27-positive AAU [ 13 , 18 ]. On the other hand, Onal et al reported that there was no significant association between gram-negative organisms and AAU [ 19 ]. In this study, we showed an inverse association between H .…”
Section: Discussionmentioning
confidence: 99%
“…pylori in the development and recurrence of HLA-B27-positive AAU [ 13 , 18 ]. On the other hand, Onal et al reported that there was no significant association between gram-negative organisms and AAU [ 19 ]. In this study, we showed an inverse association between H .…”
Section: Discussionmentioning
confidence: 99%
“…Two small serological studies did not find an association between AAU and C. trachomatis when comparing with age-matched controls, nor did they find an association with any enteric infection suspected of causing ReA ( 107 , 108 ). Neither study measured ASCAs.…”
Section: The Usual Suspectsmentioning
confidence: 93%
“…ASCAs are strongly associated with uveitis in spondyloarthritis patients ( 16 ), but antibodies against various bacteria suspected of causing ReA are not ( 107 , 108 ). Similarly, circulating CD4+ T cells in uveitis patients are more sensitive than controls to fungal antigens ( C. albicans ) after a 24-h antigen exposure period ( 127 ), whereas sensitivity to bacterial antigens ( Staphylococcus aureus, Clostridium tetani , and Mycobacterium tuberculosis ) and protist antigens ( Toxoplasma gondii ) are similar in both groups ( 127 ).…”
Section: Links With Fungimentioning
confidence: 99%
“…Liegen zusätzlich eine Konjunktivitis und eine Urethritis vor, so spricht man von einem Reiter-Syndrom. Bei erwachsenen HLA-B27-positiven oder -negativen Patienten mit isolierter akuter anteriorer Uveitis (AAU) fanden sich dagegen keine eindeutigen Assoziationen mit Infektionen durch gramnegative Bakterien [9,17], jedoch mit Chlamydia pneumoniae [10] und mit Helicobacter pylori [18,19]. Patienten mit AAU und häufigen Uveitisschüben wiesen häufiger Antikçrper gegen die untersuchten Erreger auf als Patienten ohne oder mit seltenen Uveitisrezidiven, was als Hinweis auf wiederholte Infektionen, auf Antigenpersistenz oder auf eine erhçhte Reagibilität des angeborenen Immunsystems gedeutet wurde [9].…”
Section: Infektionsassoziierte Entzündlich Rheumatische Erkrankungenunclassified